Evolutionary renovation of L/M opsin polymorphism confers a fruit discrimination advantage to ateline New World monkeys. Issue 7 (24th March 2014) - Matsumoto, Yoshifumi; Hiramatsu, Chihiro; Matsushita, Yuka; Ozawa, Norihiro; Ashino, Ryuichi; Nakata, Makiko; Kasagi, Satoshi; Di Fiore, Anthony; Schaffner, Colleen M.; Aureli, Filippo; Melin, Amanda D.; Kawamura, Shoji
Abstract New World monkeys exhibit prominent colour vision variation due to allelic polymorphism of the long‐to‐middle wavelength (L/M) opsin gene. The known spectral variation of L/M opsins in primates is broadly determined by amino acid composition at three sites: 180, 277 and 285 (the 'three‐sites' rule). However, two L/M opsin alleles found in the black‐handed spider monkeys (Ateles geoffroyi) are known exceptions, presumably due to novel mutations. The spectral separation of the two L/M photopigments is 1.5 times greater than expected based on the 'three‐sites' rule. Yet the consequence of this for the visual ecology of the species is unknown, as is the evolutionary mechanism by which spectral shift was achieved. In this study, we first examine L/M opsins of two other Atelinae species, the long‐haired spider monkeys (A. belzebuth) and the common woolly monkeys (Lagothrix lagotricha). By a series of site‐directed mutagenesis, we show that a mutation Y213D (tyrosine to aspartic acid at site 213) in the ancestral opsin of the two alleles enabled N294K, which occurred in one allele of the ateline ancestor and increased the spectral separation between the two alleles. Second, by modelling the chromaticity of dietary fruits and background leaves in a natural habitat of spider monkeys, we demonstrate that chromatic discrimination of fruit from leaves is significantly enhanced by these mutations. This evolutionary renovation of L/M opsin polymorphism in atelines illustrates a previously unappreciated dynamism of opsin genes in shaping primate colour vision.